REKONSTRUKSI PEMIKIRAN PENDIDIKAN SEBAGAI BASIS PENGUATAN PROFESIONALISME GURU GENERASI Z DI MADRASAH IBTIDAIYAH - Ahmad Rifki Maulana Adi Saputra; Muhtar Sofwan Hidayat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of education in the digital era is marked by the emergence of Generation Z teachers in elementary education institutions, including Madrasah Ibtidaiyah (MI). Generation Z teachers possess distinctive characteristics such as high digital literacy, creativity, and a preference for collaborative learning. However, these characteristics require reinforcement through a strong foundation of educational thought to ensure that teachers maintain professionalism and uphold Islamic educational values. This article aims to examine educational thought as a foundation for strengthening the role of Generation Z teachers in Madrasah Ibtidaiyah. This study employs a qualitative approach using library research methods. Data were collected from books and scholarly journal articles published within the last ten years that are relevant to educational thought, Generation Z teachers, and Madrasah Ibtidaiyah education. The findings indicate that both classical and contemporary educational thoughts play a significant role in strengthening the pedagogical, personal, social, and professional competencies of Generation Z teachers. Educational thought serves as a philosophical foundation that enables Generation Z teachers to adapt to technological advancements while maintaining moral values and Islamic identity in the learning process.